PREVALENCE OF URINARY TRACT STONES IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA (BPH) UNDERGOING TRANS URETHRAL RESECTION OF THE PROSTATE (TURP) OPERATION - Cahayani, Putu Ayu Evie; Daryanto, Besut; Gunawan, Atma (Indonesian Urological Association, 2024)
Objective: This study aims to determine the prevalence of urinary tract stones in BPH patients undergoing TURP surgery. Material & Methods: This research is a descriptive study using secondary data with medical records of BPH patients who underwent TURP at Saiful Anwar General Hospital (RSSA) for the period of 2018 – 2022. Results: From the results of the 169 patient samples BPH undergoing TURP, there were 35 samples, who experienced urinary tract stones. The most frequent incidence of urinary tract stones in patients with BPH at the age of 60 – 70 years of 15 samples (42.90 %), with the highest prostate volume being >50 mL, there are 15 samples (42.90 %), and the location of the most urinary tract stone were in the lower urinary tract with the bladder stone type being 30 samples (85.7%). Conclusion: From the results, it can be concluded that the prevalence of urinary tract stones in BPH patients undergoing TURP surgery is 20.7%, which is an absolute indication for TURP. Keywords: Benign prostatic hyperplasia, urinary tract stone, age, prostate volume.